Antithrombotic treatment and risk of complications after head and neck full thickness skin graft surgery. Issue 6 (2nd November 2018) - Hasselgren, Martin; Runer, Thomas; Janson, Peter; Ekström, Magnus
Abstract: Head and neck skin cancer surgery using a full thickness skin graft is a common procedure. Evidence concerning the effects of perioperative antithrombotic treatment on complications is limited. The aim of this study was to evaluate whether perioperative antithrombotic treatment is associated with risk of necrosis, bleeding or infection after full thickness skin graft surgery. Retrospective single-center cohort study with medical records review. Patients operated with a head and neck full thickness skin graft in 2010 and 2013–2015 had available data and were included. Any antithrombotic treatment was continued and all patients were routinely followed-up on days 7–10 after surgery. Data on demographics, concurrent disease, clinical characteristics, antithrombotic medications and postoperative necrosis, bleeding and infection were collected from electronic medical records. Associations with complications were examined using multivariate logistic regression adjusted for age, sex, reoperation, size of excision, site of surgery and concurrent disease. In total, 302 patients (53% women) were included. Antithrombotic treatment ( n  = 125 patients) was not associated with higher adjusted risk of total complications in multivariate analysis (OR 0.70; 95% CI: 0.34–1.46). In subgroup analyses, the total risk was not increased in patients on aspirin (OR 0.76; 95% CI: 0.39–1.48) or warfarin (OR 1.20; 95% CI: 0.47–3.10). In the warfarin subgroup ( N  = 26), there was a statistically non-significant trend towards increased risk of graft necrosis. This study supports that aspirin and warfarin should not be discontinued prior to head and neck full thickness skin graft surgery.